Evaluation of mineral induction ability and cytotoxicity of carbonated hydroxyapatite for pulp tissue regeneration: an in vitro study - S. Swathi Priyadharshini; Chinnasamy Ragavendran; Anand Sherwood; J. Ramana Ramya; Jogikalmat Krithikadatta (Restorative Dentistry & Endodontics)
ObjectivesThis study aimed to evaluate carbonated hydroxyapatite (CHA)’s ability for mineral induction and its in vitro cytotoxicity with human dental pulp cells.Materials and MethodsPrecursors for the study include di-ammonium hydrogen phosphate and calcium nitrate tetrahydrate, with sodium hydrogen carbonate added to achieve different levels of carbonate substitution. The synthesized CHA samples are characterized using X-ray diffraction, Fourier transform infrared spectroscopy, and Raman spectroscopy. Scanning electron microscopy (SEM) was used to observe morphology. For 14 days at 37°C, samples were submerged in simulated body fluid to assess their mineral induction capabilities. SEM was used to confirm apatite formation on sample surfaces. The cytotoxicity assay was used to assess the vitality of the cells following their exposure to various concentrations of CHA.ResultsThe Joint Committee on Powder Diffraction Standards data for HA aligned well with the results from X-ray diffraction analysis of CHA across 3 different concentrations, indicating strong agreement. Fourier transform infrared spectra indicated the presence of phosphate, hydroxyl, and carbonate groups within the samples. SEM and Energy-dispersive X-ray analysis show agglomerated and flaky nanoparticles. All the samples are bioactive, but the formation of apatite differs from one another. In vitro cytotoxicity assay showed that over 70% of cells maintain viability.ConclusionsThe results of this study may provide insight into the potential use of carbonated HA as a dental pulp-capping material for vital pulp therapy.